Ocular ischemic syndrome secondary to carotid artery disease: a comprehensive review addressing critical early detection, management, and education - Ávila-Figueroa, Eduardo; Flores-Calvo, María; Sánchez-Rodríguez, Christopher C.; Domínguez-Varela, Irving A.; Salazar-Ramírez, Patricia; Zamora Cortina, Fernanda; Tena-Betancourt, Félix E.; Anaya-Ayala, Javier E. (Frontiers in Ophthalmology, 2026)
PurposeThis study was conducted to emphasize the significance of early detection of ocular ischemic syndrome (OIS), indicating advanced carotid atherosclerotic occlusive disease and preceding life-threatening ischemic cerebrovascular events, and to boost education in eyesight care.MethodsA systematic literature search was performed using PubMed and Embase databases using the keywords “carotid disease,” “ocular ischemic syndrome,” “amaurosis fugax,” “early detection,” and education, selecting 45 articles containing relevant information for our focused review.ResultsOIS is a sight-threatening condition caused by ocular hypoperfusion, secondary to occlusive disease of the common or internal carotid arteries. We observed that this condition can be associated with multiple clinical manifestations, such as progressive or acute visual loss, orbital pain, and iris neovascularization. Carotid artery disease is frequently underdiagnosed due to an unfocused clinical examination of the eye fundus, the presence of carotid bruit, and other similarities associated with ocular ischemic syndrome, while the management of this condition should always be carried out with a multidisciplinary approach by implementing techniques such as panretinal photocoagulation (PRP), the use of ophthalmologic drugs, and surgical management of carotid via endarterectomy.ConclusionsAmong clinicians, OIS is frequently undetected because the range of symptoms initially exhibited by an individual can mimic age-related visual decline, delaying detection until serious complications such as amaurosis fugax or stroke occur. Proficient skills in fundus examination and carotid artery auscultation are crucial in identifying this harmful condition, including the use of non-invasive procedures and full recognition of the need for early eye care education.